PARAMETRIC STUDIES IN AUTOMOBILE MANUFACTURING INDUSTRY USING CELL FOCUSED PLANT LAYOUT SIMULATION APPROACH - Jayant H. Bhangale; Ashish M. Mahalle (European Scientific Journal, ESJ, 2013)
Cellular layout is having a good recognition and acceptability in manufacturing industries due to space and operator problems. Variable demand, and multi features products have driven automobile manufacturing plants to produce more with quality to face competition. Traditional manufacturing systems, such as job shops and flow lines, cannot handle such environments. Cellular manufacturing, which incorporates the flexibility of job shops and the high production rate of flow lines, has been seen as a promising alternative for such cases. Although cellular manufacturing provides great benefits, the design of cellular manufacturing systems is complex for real-life problems. Existing design methods employ simplifying assumptions which often deteriorate the validity of the models used for obtaining solutions. Two simplifying assumptions used in existing design methods are as follows. First, product mix and demand do not change over the planning horizon. Second, each operation can be performed by only one machine type, i.e., routing flexibility of parts is not considered. This research aimed to develop a model and a solution approach for designing cellular manufacturing systems that addresses these shortcomings by assuming dynamic and stochastic production requirements and employing routing flexibility.